Disorders of Language and Literacy in the Prison Population: A Scoping Review - Frøydis Morken; Lise Øen Jones; Wenche Andersen Helland (MDPI AG, 2021)
Language and literacy skills are essential for education, school achievements, work and social conditions. Some studies indicate an elevated incidence of problems with language and literacy in the prison population, potentially contributing to increased risks of maladjustment and recidivism. In general, the bulk of research on language and literacy has been directed towards children and adolescents. This study aimed to map the extent of the literature on language and literacy disorders in the adult prison population over the past 20 years, and what it reveals about the prevalence and nature of these disorders in prisoners. In total, 18 studies were identified. Of these, the majority (15) investigated literacy. The three studies investigating language all reported an elevated prevalence in the population. The literacy studies were altogether less clear, due to differences in theoretical approach and methods. In terms of the nature of the disorders, many studies assessed the behavioral level only. Results are discussed in terms of theoretical approaches, as well as recommendations for research, assessment, and intervention.